Implementasi Metode Bahtsul Masail Berbasis Pendidikan Pesantren untuk Meningkatkan Kemampuan Berpikir Kritis dan Kemampuan Menganalisis Peserta Didik pada Pembelajaran Fisika di SMA (Radiasi : Jurnal Berkala Pendidikan Fisika, 2020)
The aims of this study to (1) determine the student ability of critical think and analyze, using the bahtsul masail method, (2) to find out the difference between the bahtsul masail method and the conventional method in physics learning. The method in this study using a true experimental quantitative method with a pretest-posttest control group design. The population used was all class XI students of SMA NU Al-Ma'ruf Kudus  and samples were students of class XI MIPA 2 and MIPA 4 taken by random sampling techniques. The data collection used the pretest and posttest to determine the effect of the bahtsul masail method. The results shows (1) The student thinking ability using the Bahtsul Masail method get higher results. (2) Based on the results of data analysis using paired t-test, it is obtained tcount of -7.4828 and ttable of 1.67 with a significance level of 5% and degrees of freedom of 58 so that if t
Keywords: Metode bahtsul masail; kemampuan berpikir kritis; kemampuan menganalisis